Professional SQL server 2005 programming - Vieira, Robert (Wrox professional guides., 2007)
Professional SQL Server 2005 Programming shows experienced developers how to master the substantially revamped feature set of the latest release of Microsoft SQL Server. The book begins with a concise overview of the new features of SQL Server that is of interest to experienced developers. This is especially important given the substantial changes to SQL Server with this release. From there, the book quickly moves on to the?meat? of the title. Beginning-level material has been removed to provide more room for covering new features and more extensive code examples.